Cohort Analysis of 67 Charcot-Marie-Tooth Italian Patients: Identification of New Mutations and Broadening of Phenotype Expression Produced by Rare Variants - Ferese, Rosangela; Campopiano, Rosa; Scala, Simona; D’Alessio, Carmelo; Storto, Marianna; Buttari, Fabio; Centonze, Diego; Logroscino, Giancarlo; Zecca, Chiara; Zampatti, Stefania; Fornai, Francesco; Cianci, Vittoria; et al. (Frontiers in Genetics, 2021)
Charcot-Marie-Tooth disease (CMT) is the most prevalent inherited motor sensory neuropathy, which clusters a clinically and genetically heterogeneous group of disorders with more than 90 genes associated with different phenotypes. The goal of this study is to identify the genetic features in the recruited cohort of patients, highlighting the role of rare variants in the genotype-phenotype correlation. We enrolled 67 patients and applied a diagnostic protocol including Multiple Ligation Probe Amplification (MLPA) for Copy Number Variation (CNV) detection of PMP22 locus, and Next Generation Sequencing (NGS) for sequencing of 47 genes known to be associated with CMT and routinely screened in medical genetics. This approach allowed the identification of 26 patients carrying a whole gene CNV of PMP22. In the remaining 41 patients, NGS identified the causative variants in 8 patients in the genes HSPB1, MFN2, KIF1A, GDAP1, MTMR2, SH3TC2, KIF5A, MPZ (five new vs 3 previously reported variants; 3 sporadic vs 5 familial variants). Familial segregation analysis allowed to correctly interpret 2 variants, initially reported as “variants of uncertain significance” (VoUS) but re-classified as pathological. In this cohort, is reported a patient carrying a novel familial mutation in the Tail domain of KIF5Aa (a protein domain previously associated with familial ALS), and a CMT patient carrying a HSPB1 mutation, previously reported in ALS. These data indicate that combined tools for gene association in medical genetics allow dissecting unexpected phenotypes associated with previously known or unknown genotypes, thus broadening the phenotype expression produced by either pathogenic or undefined variants.